New Pipimorphs from the Late Cretaceous of Niger - (:unkn) unknown (My University, 2025)
In Becetèn, in southeast Niger, is one of the few mid-Upper Cretaceous (Coniacian-Santonian) fossiliferous localities in Africa where multiple anuran taxa are known. Two of them, Pachycentrata taqueti and Inbecetenanura ragei, have been described from In Becetèn. Both are pipids, a clade composed of exclusively aquatic anurans. Beside these two pipids, numerous isolated bones have also been referred to anurans within the site, but never referred to any known less inclusive taxa. Here we describe several identified cranial and postcranial bones referable to Pipidae or its stem-group, which together constitute Pipimorpha. Among these elements, three cranial elements are referred to two unnamed pipimorphs. One of these has gondwanomorph affinities (pipids + South-American and African extinct pipimorphs).These conclusions are supported by our phylogenetic analyses. Numerous postcranial elements are not referable to any of the four pipimorph taxa identified at In Becetèn, although some ilia might be tentatively referred to ?Pachycentrata sp. The presence of at least four distinct anuran taxa makes In Becetèn the most diverse anuran site in Mesozoic Africa. It is also the first site in the Mesozoic where four pipimorph taxa are identified. The dominance of pipimorphs in the anuran diversity of the site suggests that In Becetèn was likely more lacustrine than previously thought.
Keywords: African Research